A Review of the Capability to Use Technology Acceptance Theories in the Context of Ecommerce - Kandambi, G. P. H.; Wijayanayaka, W. M. J. I. (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
Technology acceptance theories are mainly focused on measuring the user adaption of new technologies. Those technology acceptance theories were using to measure online purchasing intention by researchers. It can be seen those theories were directly focused on technological components while ignoring retailer, customer, medium and most other macro characteristic engaged with online purchasing. Hence, it is mandatory to study the capability to use technology acceptance theories to measure online purchasing intention. Main technology acceptance theories were critically evaluated by considering their context applied, concept and process alignment with online purchasing to identify the uniqueness of each model. Results of the Evaluation confirmed the technology acceptance theories were directly used to measure technology acceptance behaviour in an organizational context. Further it was confirmed the differences in contexts, theoretical concepts and processes between the worker in an organization and online consumer. Finally, evaluation was confirmed, and technology acceptance theories were directly used to measure technology acceptance behaviour in an organizational context. When comparing the worker in an organisational context to the online consumer in online purchasing, there was a distinction in context, concept, process, and theoretical aspects. Therefore, it is impossible to directly measure online purchasing intention using those technology acceptance theories. Similarly, Innovation Diffusion Theory (IDT), the Unified theory of acceptance and use of technology (UTAUT2) and the theory of Reason Action (TRA) cannot be used measure online purchasing because individual consumers were engaged with new technologies such as an online game or email, and TRA requires a high level of volitional control. Therefore, it is essential to create a global model that evaluates online purchasing while maximising the theoretical underpinnings of earlier technology acceptance.